Diagnostic test accuracy of 18F-FDG PET/CT for prediction of programmed death ligand 1 (PD-L1) expression in solid tumours: a meta-analysis. Issue 11 (November 2021) - Seol, H.Y.; Kim, Y.S.; Kim, S.-J.
Abstract : AIM: To investigate the predictive value of integrated 2-[ 18 F]-fluoro-2-deoxy-d- glucose ( 18 F-FDG) positron-emission tomography/computed tomography (PET/CT) for the prediction of programmed death ligand 1 (PD-L1) expression in solid tumours via a systematic review and meta-analysis. MATERIALS AND METHODS: The PubMed, Cochrane, and EMBASE databases, from the earliest available date of indexing through 31 October 2020, were searched for studies evaluating the diagnostic performance of 18 F-FDG PET/CT for prediction of PD-L1 expression in solid tumours other than lung cancer. RESULTS: Across seven studies (473 patients), the pooled sensitivity for 18 F-FDG PET/CT was 0.75 (95% confidence interval [CI]: 0.65–0.82) without heterogeneity (I 2  = 47.2, p= 0.08) and a pooled specificity of 0.73 (95% CI: 0.64–0.81) with heterogeneity (I 2  = 53.8, p= 0.04). Likelihood ratio (LR) syntheses gave an overall positive likelihood ratio (LR+) of 2.8 (95% CI: 2.1–3.7) and negative likelihood ratio (LR–) of 0.35 (95% CI: 0.26–0.47). The pooled diagnostic odds ratio (DOR) was 8 (95% CI: 5–13). Hierarchical summary receiver operating characteristic (ROC) curve and indicates that the area under the curve was 0.80 (95% CI: 0.77–0.84). CONCLUSION: The current meta-analysis showed a moderate sensitivity and specificity of 18 F-FDG PET/CT for the prediction of PD-L1 expression in solid tumours. At present, the literature regarding the use of 18 F-FDG PET/CT for the prediction of PD-L1 expression in solid tumours still limited; thus, further large multicentre studies would be necessary to substantiate the diagnostic accuracy of 18 F-FDG PET/CT for prediction of PD-L1 expression in solid tumours. Highlights: The predictive value of F-18 FDG PET/CT was assessed for PD-L1expression. F-18 FDG PET/CT showed moderate diagnostic value. The F-18 FDG PET/CT might not be useful for PD-L1expression.